PENGARUH KOMPENSASI DAN SEMANGAT KERJA TERHADAP KINERJA KARYAWAN PADA NINJA EXPRESS BANGGAI: THE EFFECT OF COMPENSATION AND MORALE ON EMPLOYEE PERFORMANCE AT NINJA EXPRESS BANGGAI - La Saudin; Debiyanti Kune; Fitri Devi Leztari Izaak (Indonesian Journal of Economy, Business, Entrepreneurship and Finance, 2023)
The purpose of this study is to determine the effect of compensation and morale on employee performance at Ninja Express Banggai. The analytical method used in this study is a qualitative analysis method, the analytical tool used to analyze data using SPSS 25. While the data source in this study uses primary data and secondary data. Based on the results of data analysis using SPSS 25, it shows that from the results of the t test it was found that all independent variables, namely Compensation (X1), and Work Morale (X2), have a partial effect on Employee Performance (Y) at Ninja Express Banggai, From the test results ANOVA (analysis of variant) or F test obtained an F-count of 164.954 and an F-table of 3.32. With this comparison, it means that it can be seen that the F-count = 164.954 > F-table = 3.32 which means that it simultaneously has a positive effect and significant, and the results of the research partially show that the variable Morale (X2) is the variable that has the most dominant and significant influence with a coefficient value of 0.891 and a Sig value of 0.000 which means that Morale has an influence on Employee Performance (Y) at Ninja Express Banggai